Simple Additive Weighting to Determine The Best Employee in a Freight Forwarding and Logistics Company - Siahaan, Fernando; Anwar, Syaiful; W Handono, Felix (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The problem is that there is no method used to determine the best employee in the company based on the criteria set by the company. The purpose of this research is to propose simple additive weighting as a method for finding the best employees according to the weighting carried out. To make decisions, there are several criteria and criteria weights that are needed as a measuring tool to assess employees who will be promoted, attendance, QSM, Quiz, leading. Period of work and team work. The weight value of each criterion is attendance 0.20, QSM 0.25, Quiz 0.15, leading 0.20, tenure 0.10 and team work 0.10. Quality service management (QSM) if sub criteria < 200 QSM value 1, sub criteria 201 - 300 QSM value 2, sub criteria 301 - 400 QSM value 3, sub criteria 401 - 500 QSM value 4, sub criteria 501 - 600 QSM value 5. The results of the analysis with the saw method obtained two employees who got the highest score who had the right to be promoted for promotion with a value of 84.25 and 82.25. the conclusion is that the SAW method is influential in supporting and facilitating decision making to determine promoted employees.